The social gulf in the Tradiciones peruanas by Ricardo Palma - Huamán Córdova, Nataly Briyit (2019)
Following the spirit of reflection of the patriarch of Peruvian literature, this presentation will analyze the social inequality in the Tradiciones peruanas, through the interpretation of the phrases and thoughts that Ricardo Palma includes in his writings. It also intends to contextualize this topic with the social reality of our times, in order to understand the history of our problems and from there write a new path of freedom and social justice.